PELATIHAN PENELITIAN TINDAKAN KELAS (PTK) BAGI GURU SMKN 1 KECAMATAN MEMPURA KABUPATEN SIAK - Lega Putri Utami; Legisnal Hakim; Ahmad Kafrawi Nasution; Sunaryo Sunaryo; Abrar Ridwan; Budi Istana; Afdhal Afdhal; Ridwan Abdurahman (Jurnal Pengabdian UntukMu NegeRI, 2019)
Classroom Action Research (CAR) is research conducted by teachers in their own class by planning, implementing and reflecting actions collaboratively and participatively with the aim of improving performance as a teacher so that student learning outcomes can improve. Thus PTK can facilitate teachers to develop an understanding of pedagogy in order to improve their learning. This training also invites teacher friends to step into various records that after being processed can manifest into a quality study. Carry out research on what is done daily by a teacher who can finally produce a work called PTK. This can happen if a general sequence of procedures, which starts from the identification of research problems encountered until the final report is recorded. So, it is very important that this procedure is understood and adhered to by the teacher who is researching. The overall service activities are quite good in terms of the target number of participants and enthusiasm in receiving the material provided.